Impact of variant reclassification in the clinical setting of cardiovascular genetics. Issue 2 (7th October 2020) - VanDyke, Rebecca E.; Hashimoto, Sayaka; Morales, Ana; Pyatt, Robert E.; Sturm, Amy C.
Abstract: Genetic testing for cardiovascular disease (CVD) has advanced over the past ten years, but these advancements have posed new challenges in variant classification. To address these challenges, ACMG/AMP published guidelines for variant interpretation in 2015. This study aimed to determine what impact these guidelines have on variant classification in clinical cardiovascular genetics. A retrospective chart review identified patients who underwent clinical genetic testing and had a variant identified in a gene associated with CVD. For each variant, systematic evidence review was performed and ACMG guidelines were applied for classification. These classifications were compared to those provided on patients' genetic test reports. This study identified 223 unique variants in 237 patients. Seventy‐nine (35%) of the variants had classifications that differed from their clinical reports. Twenty‐eight (35%) of these reclassifications would have changed medical management recommendations for 38 patients. Application of these guidelines resulted in reclassification for approximately one‐third of the variants in this study. Clinicians can have a more active role in the process of variant classification. Variant classifications should be updated over time in the clinical CVD setting due to the impact reclassifications can have on clinical screening recommendations.